Mechanical modelling of the human abdomen following hernia surgery - Hernández Gascón, Belén; Peña Baquedano, Estefanía; Pascual González, Gemma; Bellón, Juan M.; Calvo, Begoña (Jornada de Jóvenes Investigadores del I3A, 2014)
Abdominal hernia is a frequent disease and diverse problems following hernia repair could reduce the quality of patient life. This work is projected to define a computational methodology based on experimental techniques that would help surgeons in deciding which prosthesis is the most convenient depending on the type of defect and patient.